2021
DOI: 10.48550/arxiv.2103.07171
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrafast light-induced dynamics in the microsolvated biomolecular indole chromophore with water

Abstract: Interactions between proteins and their solvent environment can be studied in a bottom-up approach using hydrogen-bonded chromophore-solvent clusters. The ultrafast dynamics following UV-lightinduced electronic excitation of the chromophores, potential radiation-damage, and their dependence on solvation are important open questions. The microsolvation effect is challenging to study due to the inherent mix of the produced gas-phase aggregates. We used the deflector to spatially separate different molecular spec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…The radiation protection mechanisms for excited chromophores were studied both experimentally and theoretically. 55,56,61,62,83 Our study showed that this protective effect observed for solvated chromophores is also valid after ionisation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The radiation protection mechanisms for excited chromophores were studied both experimentally and theoretically. 55,56,61,62,83 Our study showed that this protective effect observed for solvated chromophores is also valid after ionisation.…”
Section: Discussionsupporting
confidence: 68%
“…53 Pyrrole is also a subunit of indole, 3-methylindole, and tryptophan, which are of great relevance as the principal UV absorbers of proteins. 54,55 The photophysical and photochemical properties of indole and pyrrole are sensitive to the hydration environment: [56][57][58][59][60][61] upon UV absorption these chromophores indirectly populate an excited 1 ps* state, which is repulsive along the N-H-stretching coordinate. [54][55][56] This triggers an ultrafast internal-conversion process to the ground state, essential for the photostability of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of solvation on indole's electronic structure has long been debated [6], in particular with respect to its two lowest-energy 1 L a and 1 L b electronically excited singlet states [7][8][9]. Microsolvation experiments with one or a few water molecules attached have shed some light onto this topic [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…4 They offer an appealing way for the quantitative investigations of the effects of hydration on the photoexcitation and ionization dynamics and the mechanisms of chemical reactions in general. [5][6][7][8][9][10] First principles calculations of potential energy surfaces (PESs) for weakly-bound complexes are challenging and computationally expensive. [11][12][13][14] The presence of small energy differences in weakly-bound PES means that generally high levels of theory need to be employed to produce correct asymptotic behavior.…”
Section: Introductionmentioning
confidence: 99%